AD, Volume 17, n° 4, 1992 - Full Issue - Journal System, (Africa Development, 1992)
Contents National Security and Defense Expenditure in Africa: A Political and Economic Analysis Julius E Nyang'oro .................................5 Développement rural au Cameroun: Et si les paysans le concevaient autrement? Nyemba Ambela Jean .............................29 The Legal Control of Tertiary Institutions in East Africa: The Case of Makerere University J Oloka-Onyango ....................................... 47 Inertia in African Public Administration: An Examination of Some Causes and Remedies S K Asibuo ............................................. 67 Determinants of Entrepreneurship Development in the Urban Informal Sector of Lagos I Oluranti Ogunrinola .............................. 81 Book Reviews Patrick Manning, Slavery and African Life: Occidental, Oriental, and African Slave Trades Tiyambe Zeleza ......................................... 99 Coming to Terms with the Famine and Food Question in Eyhiopia: A Review of Rahmato Dessalegn, Famine and Survival Strategies Nyangabyaki Bazaara .............................102